The Analysis of Computational Thinking (CT) Skills of 8th Grade Students at SMP Negeri 1 Jatinangor: Computational Thinking, bilangan - Yusup Suhendar; Tita Rosita, Neneng (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2024)
Computational Thinking (CT) is a high-level thinking skill required for developing 21st-century skills. This research aims to analyze the CT skills of 8th-grade students at SMP Negeri 1 Jatinangor. The research method is qualitative with a descriptive approach. The study population includes all 8th-grade classes at SMP Negeri 1 Jatinangor registered in the odd semester of the 2024/2025 academic year. The sample for this study consists of 30 students from class VIII-A. Data was collected by administering a test with two open-ended questions that cover CT skill indicators: decomposition, pattern recognition, abstraction, and algorithms. From the data analysis, an average score of 36.15 was obtained, with a maximum score of 87.50 and a minimum score of 12.50. The CT abilities of the 8th-grade students at SMP Negeri 1 Jatinangor can be grouped as follows: 10% in the very good category, 13.33% in the good category, 33.34% in the fair category, and 43.33% in the low category. The research findings suggest that, in the very good and good categories, students have achieved all CT skill indicators, although there are minor errors in the good category. In the fair category, students have reached the decomposition indicator but have not met the others. Meanwhile, in the low category, students have not achieved any of the CT skill indicators.